Serum Vitamin D Among Patients withType 2 Diabetes Mellitus - Ahmed, Shwan Sulaiman; Sarı, Aysel (My University, 2022)
Vitamin D supplements are a beneficial health issue to benefit from insulin therapy. In those with T2DM, serum vit-D was checked and resuscitated. Serum vit-D was evaluated with its rich content. Serum vit D levels were statistically significantly lower in T2DM patients than in the control group. It was found to be significant in terms of the relationship between fasting blood sugar and vit-D and HbA1C. Vit-D in sugar will be used as a benefit from vit-D in patients with blood T2DM patients. The mean±SD vit-D level was 19.22±9.23 for the whole population with a fasting blood glucose level of 110 mg/dl or less, and 12.21±6.15 for people with a fasting blood glucose level above 130 mg/dl, and p<0.001. The relationship between vit-D level and fasting blood sugar is statistically significant with negative pearson correlation coefficient. Vit-D mean±SD 20.46±8.56 for the entire population with an HbA1C level equal to or lower than 6.5%, and 12.84±6% for individuals with a fasting blood glucose level above 6.5%, is 26 and p<0.001. The strong relationship between vit-D and fasting blood glucose and HbA1C is due to the fact that vit-D tends to specifically stimulate insulin production in ?-pancreatic cells via the nuclear vit-D receptor (VDR) and that vit-D minimizes inflammation. Vit-D supplements are a beneficial health challenge to benefit from insulin therapy. Serum vit-D was checked in patients with T2DM. The serum has been evaluated with its rich content of vit-D. Serum vit-D levels were statistically significantly lower in T2DM patients compared to the control group. It was found to be significant in terms of the relationship between fasting blood sugar and vit-D and HbA1C. Vit-D in sugar will be used as a benefit from vit-D in blood T2DM patients.
Keywords: Endokrinoloji ve Metabolizma; Mikrobiyoloji; Temel Sağlık Hizmetleri; Onkoloji; Tıbbi Laboratuar Teknolojisi